PENGARUH KONTROL DIRI TERBADAP PERILAKU MENYIMPANG PESERTA DIDIK KELAS VllI Dl SMP NEGERI26 PADANG - Yulni, Misri - (Bimbingan dan Konseling, 2014)
Â This research is motivated by the phenomenon that researchers found during the practice field. Based on this phenomeno